Diagnóstico por imagem: nível de conhecimento e uso racional entre médicos da atenção básica e médicos residentes. - MEMÓRIA, Thiara Castro de Oliveira (2021)
Introduction: In view of technological-scientific advances, the patient's demand for more tests and greater availability and functionality of imaging methods, in addition to the aging and clinical complexity of the population, there has been and continues to be a significant growth in diagnostic imaging tests and services in recent decades. There is a lack of standardization of radiology teaching in institutions, pointing to the need to reassess the medical curricula to ensure the rational, conscious and effective use of image resources, with benefits for the doctor, the patient and the health system. Objective: To assess the level of knowledge of primary care physicians and internal medicine residents about imaging tests as well as their rational use through the correct indication of methods in clinical situations of daily practice, comparing the two groups and also with variables socio-demographic and professional performance and training. Materials and Methods: Study conducted with 123 physicians, members of primary health care and/or residents of a medical clinic in São Luis, MA, through a structured questionnaire containing questions about general knowledge and indication of imaging methods. This is a quantitative, cross-sectional, analytical, observational, non-interventionist study. The average of correct answers or percentage of correct answers (%avg = percentage average.) of the physicians was used in the questions in the questionnaires, as well as a comparative analysis of the %p.a according to the variables of professional performance and training. For the analysis of the significance of satisfactory hits, a satisfactory reference value (RV) of 80% was considered. Shapiro-Wilk normality tests and Bartlett's homogeneity of variance tests, both at 5% significance, were performed to verify the possibility of performing Student's T tests and Analysis of Variance (ANOVA) with Tukey's post hoc test (CALLEGARI-JACQUES, 2003). All data were tabulated in Excel 2016 spreadsheet and tests performed in the IBM SPSS 24 program (IBM SPSS Statistics, 2016) at 5% significance.Results: The majority were female (55.3%; n=68), aged 20 to 30 years (44.7%; n=55), being 65 (52.8%) from primary care (AB) and 58 residents (47.2%), with 63.4% working in emergency services. There was a higher level of knowledge expressed by average of correct answers in percentual among the group of resident physicians (%avg=85.7+-6.4) when compared to AB physicians (%avg=78.2+-15), with less time since graduation (%avg=83.35+11.1) Better indication of tests was observed among resident physicians 85.99±8.22 versus AB physicians(%avg 77.40 ± 14.31) with p <0.001. Physicians working in the emergency department (%avg=84.70) had higher averages in better indication of tests. Final considerations: Knowledge about imaging methods and proper ordering are essential for quality medical care, as their incorrect use can affect patient care and expose them to unnecessary risks, in addition to delaying diagnosis and treatment. Radiology is among the medical specialties that have undergone the most changes as a result of technological advances.